In vitro effect of murine-derived transfer factor on Salmonella-specific rosette formation. - Smith, R A (1982)
The splenic lymphocytes from Salmonella-immune ICR Swiss or C3H/HeJ mice formed greater than 0.2% antigen-specific rosettes with sheep erythrocytes coated with a spent-medium protein antigen of Salmonella typhimurium. These rosette-forming lymphocytes were found to be sensitive to the effects of antithymocyte serum plus complement. Transfer factor prepared from the Salmonella-immune splenic lymphocytes of ICR Swiss mice was active in sensitizing nonimmune ICR Swiss or C3H/HeJ lymphocytes to form greater than or equal to 0.2% rosettes with salmonella antigen-coated sheep erythrocytes. These rosettes were also sensitive to antithymocyte serum and complement. Few rosettes were formed between the transfer factor-treated lymphocytes and sheep erythrocytes coated with a Listeria protein antigen. A nonimmune dialysate preparation was inactive in sensitizing nonimmune lymphocytes, as indicated by a lack of rosette formation. Neither the immune transfer factor nor the nonimmune dialysate had any enhancing or abrogating effect upon rosette formation by splenic lymphocytes from Salmonella-immune mice. The enumeration of antigen-specific rosettes may be a useful means of assaying for transfer factor activity.